Dorstenia acangatara (Moraceae), a new and threatened species from Southeastern Brazil - Vianna F., Marcelo D. M.; Dos Santos, Alessandra; Machado, Anderson F. P.; Mansano, Vidal De Freitas; Neto, Sergio Romaniuc (Phytotaxa, 2013)
Dorstenia acangatara (Moraceae), a new species, endemic to the Atlantic rainforest between Espírito Santo and Minas Gerais states, in Southeastern Brazil is described and illustrated. D. acangatara is considered threatened by IUCN standards due to its restricted geographic area of occurrence.